Rehabilitation Tourism Opportunities in the Russian Federation for Recovering COVID-19 Patients - OSADCHUK, Mikhail A.; TRUSHIN, Maxim V.; OSADCHUK, Alexey M.; MIRONOVA, Ekaterina D.; SOLODENKOVA, Karina S.; LAZAREVA, Alisa E. (Journal of Environmental Management and Tourism; Vol 11 No 7 (2020): JEMT Volume XI Issue 7(47) Winter 2020DO - 10.14505//jemt.v11.7(47).25, 2020)
The COVID-19 pandemic determined the necessity for prompt diagnostics and optimal routing of patients, followed by rehabilitation and secondary prevention, as domestic tourism intensifies. The epidemic increased the importance of digital systems for the tourism service market. Digitalization took leading positions in the tourism industry and made market participants adapt to these changes for optimizing their activities and increasing revenues. Further development of tourism in Russia, giving the ongoing pandemic, would require digital technologies such as multilanguage informational services overcoming language barriers, digital tourist cards, mobile apps introducing cultural and national landmarks online, web services for preparing tourist routes. Judging from scientific and practical experience, we can expect that medical, social, physical and psychological rehabilitation supervised by medical personnel will improve body functioning including heart, lungs, central nervous system as well as restore patients’ quality of life in general.